Kontrol Proportional Integral Derivative (PID) Sebagai Penstabil Tegangan pada Pembangkit Listrik Tenaga Hybrid - Al Aziz, Muhammad Arif; Prasetyo Hidayat, Edy; Munadhif, Ii (Rekayasa, 2022)
Around 66% of power plants in Indonesia are still sourced from coal and oil. On the other hand, Indonesia is rich in renewable energy potential but still has minimal utilization. Furthermore, the voltage at power plants that are small and less stable is also often a nuisance. Thus, an innovative hybrid, solar and hydroelectric power plant with a PID (Proportional Integral Derivative) based voltage stabilizer was created. PID-based voltage stabilizer control is generated in the form of PWM (Pulse Width Modulation). The results obtained in this study are PID control can produce the lowest voltage of 12.78 V and the highest voltage of 13.96 V with a setpoint of 13.4 V. The power generated from solar, hydro, and hybrid power plants is 11.8 Watts, 9.4 Watts, and 14.85 Watts. As for Charging the Battery, an increase of 2.72 V was obtained in 24 hours. As for the storage side, the Battery can supply a 15 watt incandescent lamp for 8 hours 55 minutes while leaving 20% of the total capacity.